2018
DOI: 10.1186/s40816-018-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antimicrobial and immunomodulatory activities of termite associated fungi, Termitomyces clypeatus R. Heim (Lyophyllaceae, Basidiomycota)

Abstract: Background: Termitomyces clypeatus (T. clypeatus) is an edible mushroom specie which grows in various areas in Cameroon. It is indicated by several healers in treatment of several infectionsand is frequently used for this purpose. However, no study has been reported on its antibacterial and immunomodulatory activities which were the aim of this study. Methods: Disc diffusion method was used to appreciate the bactericidal activity against 4 bacteria and 2 yeast species. The immunomodulatory activities were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A series of defences helps secure that fungus gardens are diseasefree, including avoidance of antagonists by the termites, 34 burial of unwanted fungi, 36 and utilisation of antimicrobial compounds of termite, Termitomyces, and bacterial origins. 23,24,37 3 Natural products reported from the termite symbiosis Our extensive literature survey from 1972 to 2020 revealed that 375 natural products have been identied in the fungus-farming termite symbiosis. Subsequent literature screening of hundreds of scientic papers allowed us to generate a searchable database of all compounds (ESI, Table 1 †) that includes molecular formulas, mass, compound name, natural product class, the producing organism and termite host (when known), geographic origin of discovery, method of identication, and known bioactivities or lack thereof.…”
Section: The Fungus-farming Termite Symbiosismentioning
confidence: 99%
See 3 more Smart Citations
“…A series of defences helps secure that fungus gardens are diseasefree, including avoidance of antagonists by the termites, 34 burial of unwanted fungi, 36 and utilisation of antimicrobial compounds of termite, Termitomyces, and bacterial origins. 23,24,37 3 Natural products reported from the termite symbiosis Our extensive literature survey from 1972 to 2020 revealed that 375 natural products have been identied in the fungus-farming termite symbiosis. Subsequent literature screening of hundreds of scientic papers allowed us to generate a searchable database of all compounds (ESI, Table 1 †) that includes molecular formulas, mass, compound name, natural product class, the producing organism and termite host (when known), geographic origin of discovery, method of identication, and known bioactivities or lack thereof.…”
Section: The Fungus-farming Termite Symbiosismentioning
confidence: 99%
“…83 It is thus conceivable that combinations of multiple compounds play a signicant role in termite nest defence through contributions to the antimicrobial activity observed in Termitomyces. 24,84 Phenolic compounds are found widely throughout the plant kingdom, and it is possible that the phenolic compounds identied in Termitomyces could have been synthesized and absorbed from plants. However, the Shikimate pathway has been correlated to the presence of phenolic compounds in fungi 85,86 and a recent study showed that despite avonoids being well-known plant metabolites, all genes and protein sequences associated with the biosynthesis of avonoids can be found in some fungi.…”
Section: Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Russulales) reported in the reserve could be studied for production of industrial and bioactive agents. Furthermore, Jumbam et al [28] reported that only three records of the saprotrophic genus Hericium (in family Hericiaceae of Russulales) are available from Africa.…”
Section: Nbmentioning
confidence: 99%